Ответы и объяснения

2013-07-30T14:15:34+04:00
2013-07-30T18:08:19+04:00



а)6х*(3х-5у)          6х        6*(-4)          -24 
----------------- =--------------=  ----------- =   ----------   =240        
у*(3х-5у)               у            (-0,1)      -0,1



б)(х+5у)^2       х+5у       -4+5*(-0,1)     
--------------=--------------=-----------------------= -1,5
3*(х+5у)           3                   3

в)(2х+3у)*(2х-3у)          2х+3у       2*(-4)+3*(-0,1)         -8+(-0,3)       -8,3         83   
-------------------------=--------------------=---------------------------=-------------= ------------=- ----------=
6ху*(2х-3у)                6ху               6*(-4)*(-0,1)           2,4             2,4          24 
   
= -3 11/24

г)(х+у)*(х+у)        х+у        -4+(-0,1)      -4,1       41
----------------------=------------=-----------------=---------=----------=1 2/39
(х-у)*(х+у)          х-у          (-4)-(-0,1)     -3,9       39